Experiential reflective learning and comfort zone - Jan Nehyba (Czech Pedagogical Society, 2011)
The article deals with the issue of experiential reflective learning. Firstlyit aims to discuss the concept of comfort zone in this area. It goes beyond the usualdefinition of the domestic comfort zone and it reflects in terms of experiential reflectivelearning in the world. The conclusions point to possible parallels with the concept ofcomfort zones and K. Lewin theory. Overall, the article focuses on topics that help toexpand the view on the issue of comfort zone.